Sol T. Plaatje's paremiological quest: A common humanity in cultural diversity. - Makhudu, Khekhethi (Tydskrif vir Letterkunde, 2018)
Having written and compiled, from memory, over 700 Setswana proverbs when he was resident in London during the second decade of 1900, Sol T. Plaatje exhibited unusual ethnographic knowledge and remarkable, creative translation skills in diasporalike circumstances. While most literary researchers attest to those achievements, few have been the theories to account sufficiently for Plaatje's multilingual proverb renditions. The view propounded here is that Plaatje's paremiological enterprise was probably never only an exercise of his polyglot abilities. Rather his quest apparently was to assert the similarities and convergences between African and European people's cultural histories. Deep pride in his Setswana identity seems to have propelled a need to highlight the ethnographic bonds Northern and Southern nations share. For Plaatje, seeing overlaps and equivalences in the proverbs of European and the Batswana peoples, firstly validates orality as the bedrock of modern literary expression. Secondly, the relationship of the two appears to recapitulate the communicative connections of people, across time and space. Lastly, the point is made that Plaatje's search for unity in linguistic and cultural diversity, as exhibited in the Diane tsa Setswana collection (1916) and A Sechuana Reader stories (1924), provides instructive lessons which present-day South Africa would ill afford to ignore considering the social cohesion challenges the nation faces.